Hubungan Kualitas Tidur dengan Atensi pada Mahasiswa/ i Fakultas Kedokteran Universitas HKBP Nommensen Medan - Yola Anggika Surbakti; Jenny Novina Sitepu; Johan C Silaen (Universitas HKBP Nommensen, 2020)
Background: Attention is one component of cognitive function that consists of three aspects, such as alerting, orienting and executive attention. Attention failure is thought to be a major cause of cognitive decline in sleep deprivation Objective: To determine the relationship between sleep quality and attention on students of the Faculty of Medicine, Universitas HKBP Nommensen Method: This study was an observational analytic study using a cross-sectional design. Study population was active students of the Faculty of Medicine, Universitas HKBP Nommensen. The sample was 62 respondents who met the inclusion and exclusion criteria. Data was collected by giving and filling out the Pittsburgh Sleep Quality Index (PSQI) questionnaire to assess sleep quality. Then proceed with attention checks using Attention Network Test (ANT). The relationship between sleep quality and attention was analyzed using Spearman test. Results: Respondents who have good sleep quality was 34 respondents (54.8%), moderate sleep quality was 24 respondents (38.6%, and poor sleep quality was 4 respondents (6.4%). Median epiction of orienting based on good sleep quality was 28.00 ms and poor sleep quality was 32.00 ms. Median depiction of executive attention based on good sleep quality was 142.29 ms and poor sleep quality was 170.00 ms. There was no correlation between sleep quality with alerting (p = 0.631 and r = 0.062), orienting (p = 0.892 and r = 0.018) and executive attention (p = 0.085 and r = 0.221) Conclusion: There is no relationship between sleep quality and attention (alerting, orienting and executive attention).